The Effect of Convenience, Comfort and Risk on the Preferences of Independent Learning–Independent Campus (MBKM) Students in Using QRIS - Nugraha, Muhammad Adhitya; Hilendri, Baiq Anggun (International Journal of Business and Applied Economics, 2024)
This study aims to analyze the convenience, comfort and risks of the preferences of independent learning students on an independent campus (MBKM) in using QRIS. The research method used is quantitative with a descriptive approach. Data collection techniques through the distribution of questionnaires. The sample in this study is MBKM students exchange Bacht 3 students. The results of this study show that convenience, comfort, and risk have a significant positive effect on the preferences of independent students to study on an independent campus in using QRIS with  an R – Square  score of 0.652 or 65.2 %, indicating that the preferences of MBKM students in using QRIS are influenced by Convenience, Convenience, and Risk in this study.